(untitled) (The Journal of Psychology and Sociology, 2013)
There is quite often the incurable (terminal) patient in a hospice which days are considered. The person – a unique live being which knows about inevitability of death. Fear of death – feeling natural. When the death appears suddenly close and inevitable to meet her difficultly. To illness displays very heavy mental condition – fear of death, fear of uncertainty increases. Worst of all, if the patient gives in to a panic. Then it is necessary – to observe one how symptoms of illness develop and as weakens and the body perishes; there will be sleepless nights both more and more deep melancholy and despair.